Molecular epidemiology of salmonella enterica serovar typhi isolates from Kelantan, Malaysia using variable number tandem repeat (VNTR) - Zalati, C.W. Salma C.W. (2016)
The capability to strain type bacterial isolates is a critical tool in epidemiological investigation in order to control their dissemination. A number of strain typing methods have been developed for Salmonella enterica serovar Typhi (S. enterica ser. Typhi) such as ribotyping, Pulsed-Field Gel Electrophoresis (PFGE), Random Amplification of Polymorphic DNA (RAPD), Amplified Fragment Length Polymorphism (AFLP) and Variable Number Tandem Repeat (VNTR). The PFGE method has been considered as the gold standard method for Salmonella typing with excellent discriminatory power. However, this method has some limitations including labour intensive, time consuming and requires skilled technicians as well as expensive equipment. Therefore, in this study, a multiplex Polymerase Chain Reaction (mPCR) method incorporating primers flanking to the VNTR loci was developed for molecular typing of 200 S. enterica ser. Typhi isolates from Kelantan, Malaysia. The VNTR profiles produced could be easily analysed by visual inspection after conventional gel electrophoresis. The analysis of DNA sequence and determination of VNTR copy number of the respective repeat were performed by using ChromasPro and Tandem Repeat Finder Software. Cluster analysis was performed by using Fingerprinting Quest Software version 5.10 (Bio-Rad, USA) to study the relationship between all S. enterica ser. Typhi isolates. This study revealed that only two potential VNTR loci, TR1 and TR2, can be used as molecular markers for strain typing of S. enterica ser. Typhi isolates from Kelantan. A total of 200 isolates were able to be segregated into 38 VNTR patterns (VNTR01-VNTR38) where each pattern was considered as a distinct strain of S. enterica ser. Typhi. The S. enterica ser. Typhi strain VNTR14 has been identified as the predominant strain that predominate this state. The source of infection most probably came from typhoid carriers since strains found in carrier isolates were also found in acute isolates. Multiple strains were identified from outbreak and sporadic cases of typhoid fever which suggests that these cases were due to different sources of infection. The typhoid infection that occurred in each household shared the same VNTR pattern which suggests that they were being infected from the same strain. All of the 38 S. enterica ser. Typhi strains have different VNTR copy numbers for each locus in which 7-bp repeat unit ranging from 5 to 19 copies and 8-bp repeat unit ranging from 7 to 42 copies were observed in TR1 and TR2 loci. As the conclusion, the VNTR method established in this study provides a simple, rapid, cost-effective and high discriminatory power for typing the S. enterica ser. Typhi